An internet portal for the development of clinical practice guidelines - Höhne, W.J.; Karge, T.; Siegmund, B.; Preiss, J.; Hoffmann, J.C.; Zeitz, M.; Fölsch, U.R. (Applied Clinical Informatics, 2010)
Background: The complexity and quality requirements for the development of clinical practice guidelines steadily increase. Internet technologies support this process by optimizing the development process.Objective: The aim of this internet based solution was to facilitate the development of clinical practice guidelines.Methods: An internet portal was developed allowing for a shared workplace to support clinical practice guideline authoring. It is based on a Content Management System and combines different tools for document handling and editing, communication as well as process and team steering.Results: Until now, the internet portal has been successfully implicated in the development of six evidence- and consensus-based clinical practice guidelines. Additional German and European clinical practice guidelines are currently generated with support of the internet portal. The available tools allow for a flexible design of the scheduled workflow, depending on the requirements of the respective group. An additional strength of the platform is the advantage to transfer all data from a previous version of a guideline into the next ‘life-cycle‘.Conclusion: The application of the portal results in a considerable reduction of costs and development time of the resulting clinical practice guidelines.
Keywords: Clinical practice guideline; internet portal; authoring; voting; quality management